INTEREST AND DETERMINING FACTORS FOR DIGITAL PRODUCT ADOPTION: A CASE OF TAPE MAKERS IN MALANG, INDONESIA - M Zul Mazwan; Livia Widiana; Ratri Wahyu Noviandini (Socio-Economics/Agribusiness Department, 2022)
Marketing using digital products is one way to do marketing through social media that uses the internet. The purpose of this study was to determine the interest of tape makers in the use of digital products and the factors that influence them. The sampling method used the survey method and obtained 45 respondents of tape makers on the scale of Micro, Small and Medium Enterprises (MSMEs) in Banjarsari Village, Ngajum District, Malang Regency. The descriptive analysis method is used to analyze the interest of tape makers in the use of digital products. While Partial Least Square (PLS) analysis is used to analyze the factors that influence the interest of tape makers in digital products. The results showed that tape makers have an interest in digital products in marketing tape. However, tape makers are not interested in applying or using digital information products in marketing tape. This is due to several factors that influence significantly, including advances in information technology, the ability of tape makers, environment, competition, and capital.